2002
DOI: 10.1038/sj.bmt.1703652
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine/melphalan conditioning for allogeneic transplantation in patients with multiple myeloma

Abstract: Summary:The purpose of the study was to determine the feasibility and efficacy of a reduced intensity conditioning regimen of fludarabine and melphalan for allogeneic transplantation in patients with multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 49 publications
7
74
1
2
Order By: Relevance
“…Even if the true value of lenalidomide post allograft can only be determined by a prospective randomised study, the relative long PFS of 52% at 3 years is higher than the reported 3-year PFS in similar allogeneic studies without lenalidomide. 2,3,8,9 In the current trial, neither del 13q14 or the use of mismatch donors could be identified as risk factor for survival. As data about t(4;14) or 17p were not available in all patients, a detailed cytogenetic impact could not be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the true value of lenalidomide post allograft can only be determined by a prospective randomised study, the relative long PFS of 52% at 3 years is higher than the reported 3-year PFS in similar allogeneic studies without lenalidomide. 2,3,8,9 In the current trial, neither del 13q14 or the use of mismatch donors could be identified as risk factor for survival. As data about t(4;14) or 17p were not available in all patients, a detailed cytogenetic impact could not be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In comparison to standard myeloablative conditioning regimen, reduced-intensity conditioning regimen resulted in lower non-relapse mortality (NRM) but also in a higher risk of relapse. 9 Retrospective studies suggest that the intensity of the conditioning regimen correlates with the risk of relapse.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Two German studies and a study from the MD Anderson center confirmed 2-year survivals of 26-50% for patients who had failed one or more autologous transplants. A study combining data from several centers, including approximately 120 patients, found that relapse from a prior autologous transplant was the most significant risk factor for transplant mortality (HR 2.80; P = 0.02), relapse (HR 4.14; P < 0.001), and death (HR 2.69; P = 0.005).…”
Section: Non-ablative Allogeneic Transplantsmentioning
confidence: 99%
“…[21] Several other studies of reduced-intensity allografts from family members or unrelated donors have confirmed that results are poor when patients have failed a prior autologous transplant or have chemotherapy-resistant disease. [22][23][24] Two German studies and a study from the MD Anderson center confirmed 2-year survivals of 26-50% for patients who had failed one or more autologous transplants. A study combining data from several centers, including approximately 120 patients, found that relapse from a prior autologous transplant was the most significant risk factor for transplant mortality (HR 2.80; P = 0.02), relapse (HR 4.14; P < 0.001), and death (HR 2.69; P = 0.005).…”
Section: Non-ablative Allogeneic Transplantsmentioning
confidence: 99%
“…21,22 Thus in the 2000s, more patients received allotransplant using RIC regimens, usually with melphalan 100-140 mg/m 2 with or without other agents. 23 A CIBMTR (Center for International Blood and Marrow Transplant Research) analysis demonstrated a major practice switch to nonmyeloablative and RIC-based allo-SCT with concomitant reduction in the number of myeloablative allografts performed in the years 2001-2005 compared with the two preceding 5-year intervals.…”
Section: Non-myeloablative/reduced-intensity Conditioningmentioning
confidence: 99%